The Digitalization of MSMEs: An Efforts to Improve the Regional Economy During and the Post-Covid-19 in Pangkalpinang - Belinda; Alvi Pradanita Zahri; Mutia Andini; Nizwan Zukhri (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
Micro, Small and Medium Enterprises (MSMEs) are one of the drivers of the economic development of a region. This study aims to inventory and map the implementation of digitizing MSMEs in Pangkalpinang City and to manifest strategies so that MSMEs in Pangkalpinang City can switch to the internet or digital market. The method used in this research is descriptive analysis method with a qualitative approach. Subjects or informants in this study amounted to 100 subjects from 28,259 SMEs in Pangkalpinang City obtained using purposive sampling technique. The criteria for taking the subject are (1) MSMEs located in Pangkalpinang City and registered with the Office of Cooperatives, MSMEs, and Trade in Pangkalpinang City; (2) MSMEs that include complete information at the Office of Cooperatives, MSMEs, and Trade in Pangkalpinang City; and (3) MSMEs who can be contacted via WhatsApp in accordance with data from the Pangkalpinang City Cooperatives, MSMEs and Trade Office and can be found directly. The data collection technique used is bydistributing questionnaires, observations (observations), and literature studies (library). The content analysis technique used is in the form of content analysis. Based on the research results show that The 100 MSME actors in Pangkalpinang City who were used as subjects in this study were quite good and almost evenly distributed. Strategies that can be taken by the government in order to attract MSME actors in Pangkalpinang city to switch to the internet or digital market are: (1) Providing knowledge and assistance so that MSME actors know that online promotion can reduce promotional costs; (2) Cooperating with financial technology companies related to the use of QRIS (Quick Response Code Indonesian Standard) in order to provide knowledge to MSME actors regarding the ease of digital transactions; and (3) Holding workshops for MSME actors so that they can continue to hone their abilities and skills in entrepreneurship. Keywords: MSMEs, digitization, digitalization implementation strategies, MSME performance.